Plan de emergencia y contingencia del jardín infantil Fernando Savater, según las normativas vigentes (2023)
This applied project aims to review the emergency and contingency plan that currently implements the Fernando Savater kindergarten. Having said the above, implement a documentary review, review of the structure and consequently this project will allow an analysis of compliance with the standards established by the different government entities for emergency and contingency plans that organizations must comply.